The Implementation of Wordwall Anagram Game to Improve Students Vocabulary Mastery (Scripta : English Department Journal, 2026)
This study aimed to determine whether students' vocabulary mastery at SD Aisyiyah 1 Pagaralam's fourth grade was considerably enhanced by the use of the Wordwall Anagram Game. Because it helps students comprehend and utilize English successfully in communication, vocabulary mastery is regarded as a crucial part of language learning. Nonetheless, a lot of elementary school pupils still struggle with learning, pronouncing, and comprehending English terminology. Thus, to increase students' motivation and vocabulary achievement, interactive and game-based learning materials are required. This study used a quasi-experimental design with a quantitative approach. There were 78 fourth-graders in the population, and 53 kids in the sample were split into two groups: class class IV.B as the control group and class IV.A as the experimental group. The Wordwall Anagram Game was used to instruct the experimental group, while traditional teaching techniques were used to instruct the control group. A vocabulary test with thirty multiple-choice questions that was given as a pre-test and post-test served as the study's instrument. Using SPSS version 25, descriptive statistics, the paired sample t-test, and the independent sample t-test were used to eval_uate the data. The results demonstrated that the experimental group outperformed the control group in terms of improvement. Thus, it can be said that using the Wordwall Anagram Game helped pupils become more proficient in vocabulary.